Enhanced mechanical performances and bioactivity of cell laden-graphene oxide/alginate hydrogels open new scenario for articular tissue engineering applications. (May 2017) - Marrella, A.; Lagazzo, A.; Barberis, F.; Catelani, T.; Quarto, R.; Scaglione, S.
Abstract: The development of novel 3D systems is crucial for engineering artificial tissues since the behavior of cells growth on 2D cell culture substrates does not accurately reflect that of the physiological microenvironment. In this regard, desirable 3D composites should offer tunable structural and functional properties to support appropriate cellular growth and biomechanical loads. In this work, we realized 3D alginate hydrogels functionalized with graphene oxide (GO) nanosheets for the creation of cell laden hybrid materials with proper mechanical properties for tissue engineering applications. We monitored the mechanical proprieties of 2 wt% GO/Alg hydrogels up to one month demonstrating a significant improvement of the compressive elastic modulus reaching values of 300 KPa (6 times higher stiffness), which are close to those of articular tissues. This finding has been correlated to increased intermolecular hydrogen bonds over time between GO and Alg, observed through FT-IR analysis. Interestingly, we show that 3D GO/Alg hydrogels trigger cellular activity in vitro, as demonstrated by the statistically significant improvement of the viability of fibroblasts encapsulated in GO/Alg hydrogels and by the absence of cytotoxicity of suspended GO flakes. All these findings indicate that GO/Alg hydrogel is a promising material for articular tissue engineering, where biomechanical requirements are crucial. Graphical abstract: